Semiotik Sebagai Dasar Kemampuan Komunikasi dalam Pemecahan Masalah Matematika - Suci Yongki Setyowati (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2023)
Semiotics is one of the communication science branches studying about the symbol processing into information. This information has important role in the communication course. In this case, mathematics is so closely related to the study of symbols, signs and the meaning of signs which are a series of information used for communication. These study of symbols, signs and the signs meaning are used in the communication activity especially in solving mathematical problems. In this research, researcher will investigate about communication which is obtained from the semiotic process in the signs processing into information that is useful in solving mathematical problems. Based on the results of the research done, it was found that the 4 subjects that were investigated showed the various results of the semiotic process formed in communication activity. There were subjects who could process all semiotic processes correctly so that the produced communication skills became correct information. However, there were several subjects of the research who failed in some semiotic processes, so it caused the occurred communication produced incorrect or inaccurate information.